The Javanese of Tegal Dialect Going to be the Tegal Language - Fahruroji (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the Javanese language of the Tegal dialect, which wants to become a Tegal Language. Javanese has a variety of dialects which sometimes differ from one dialect to another which has a unique difference and has a morpheme that is much different from the standard Javanese language (Surakarta - Yogyakarta). The Javanese language of Tegal dialect is Javanese that is used by the people of Tegal and surrounding areas. And, which is usually included in this dialect is the area of Tegal City, Tegal Regency, Brebes Regency and western Pemalang Regency. This research is limited to morpheme problems related to pronouns. The method used in this paper is descriptive method with data collection techniques are documents with data sources written documents. The results showed that Javanese Tegal dialect has its own characteristics that are different from standard Javanese. First person singular pronouns: enyong / inyong (Jws: kula; Ind: saya, aku; Eng: I); first person plural pronouns: awake dewek (Jws: kita; Ind: kami, kita; Eng: we); second person singular pronouns: koen (Jws: kowe / sampeyan; Ind: kamu, engkau; Eng: you, you); second person plural pronouns: koen kabeh; (Jws: kowe kabeh; Ind: kamu sekalian, kalian; Eng:you); thirdperson singular pronouns: wong kae (Jws: wong iki / dheweke; Ind: dia; Eng: he/she) and plural third person pronouns: wong-wong kae (Jws: wong-wong kui / wong-wong iku; Ind: mereka; Eng: they). Seeing this reality, is it possible that the Tegal dialect of Javanese can stand alone as a Tegal language?